Penguatan Komunikasi Efektif: Edukasi Kesehatan Reproduksi Kalangan Remaja sebagai Upaya Pencegahan Perilaku Berisiko HIV - Afina Ruqayyah; Rico Fernando Siregar; Indah Fajar Rosalina (Yayasan Literasi Sains Indonesia, 2025)
Adolescence is a crucial period in human life, characterised by the transition from childhood to adulthood. During this phase, adolescents often encounter various challenges, including those related to sexual behaviour. The sexual behaviours exhibited by adolescents can carry high risks and negatively impact their reproductive health, such as the risk of contracting HIV/AIDS and the possibility of unintended pregnancies. The implementation of this community service programme is conducted through a series of structured stages. These stages include the development of educational media, the delivery of information using animated video media, and mentoring carried out in collaboration with organisations focused on HIV prevention. In this programme, information regarding HIV is conveyed to 22 students who are members of the Student Council (OSIS) at SMK Negeri 2 Tangerang. The process of delivering information is conducted through several steps, beginning with the administration of a pre-test to assess the students' initial knowledge, followed by education presented in the form of animated videos, and concluding with a post-test to evaluate the understanding gained after participating in the programme. The results of this community service programme indicate an increase in the students' knowledge regarding HIV, as well as a change in attitudes related to the transmission of the HIV virus before and after the information was provided.